(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In the article, based on the study of scientific literature, an analysis of works on the physical fitness of handball players was carried out. The problems of assessing physical fitness, optimizing the training process, increasing the effectiveness of the game and preventing injuries are noted. It was found out that a special place in the handball training system belongs to physical training, which determines the possibilities of effective and rational execution of game techniques by each player in competitions. It is emphasized that handball is a complex coordination sport that requires a high level of development of physical qualities: speed, strength, endurance, flexibility, coordination, as well as technical and tactical skills, and the problem of assessing physical fitness is to create an objective and comprehensive system that allows not only to determine the current state of a handball player, but also to predict his further development. It is highlighted that the main problem of assessing physical fitness in handball is the need to develop an objective, comprehensive and accessible system that would meet the needs of modern sports and contribute to the effective development of handball players. It was found that to assess the level of physical fitness of handball players, tests should be used, the results of which have a reliable direct or indirect relationship with the components of competitive activity. On the basis of the results of the correlation analysis of indicators of general and special physical fitness, components of competitive activity and the comparative analysis of indicators of physical fitness among handball players of different qualifications, there are reasons to recommend that handball coaches use it in the preparatory period for the main competitions, in order to study the level of physical fitness.